2012
DOI: 10.7314/apjcp.2012.13.8.3983
|View full text |Cite
|
Sign up to set email alerts
|

Participation and Barriers to Colorectal Cancer Screening in Malaysia

Abstract: In Malaysia, colorectal cancer is the most common cancer in males and the third most common in females. Mortality due to colorectal cancer can be effectively reduced with early diagnosis. This study was designed to look into colorectal cancer screening participation and its barriers among average risk individuals in Malaysia. .0%), respectively. There were 11.2% of respondents who never received any advice to do screening. The main reason for them to undergo screening was being advised by health care provider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 24 publications
1
44
0
Order By: Relevance
“…The low rates of offering colorectal cancer screening to FDRs of CRC patients in the present study seems notable given the consistently reported failure of patients to follow the health care provider's advice leading remarkably low uptake rates even if the high proportion of patients have been advised appropriately (Yusoff et al, 2012). In a past study on FDRs of patients with CRC, it was reported that screening colonoscopies were performed only in 32% of parents (60.1% before the index case, 39.9% after the index case) and in 39% of siblings (31.7% before the index case, 68.3% after the index case) (Ruthotto et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…The low rates of offering colorectal cancer screening to FDRs of CRC patients in the present study seems notable given the consistently reported failure of patients to follow the health care provider's advice leading remarkably low uptake rates even if the high proportion of patients have been advised appropriately (Yusoff et al, 2012). In a past study on FDRs of patients with CRC, it was reported that screening colonoscopies were performed only in 32% of parents (60.1% before the index case, 39.9% after the index case) and in 39% of siblings (31.7% before the index case, 68.3% after the index case) (Ruthotto et al, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…This is of extreme importance as many people are highly influenced by physicians in health decision making [14,18]. Interestingly, Leung et al [13] discovered that the poor dissemination of CRC information among the [6], Farooqui et al [7], Hilmi et al [8], Kong et al [9], Loh et al [10], Yusoff et al [11], Koo et al [5], Harmy et al [12], Leung et al [13], Foo et al [14], Deng et al [15], Javadzade et al [16], Khayyat et al [17], Tastan et al [18], Salimzadeh et al [19], Salimzadeh et al [20] Abdullah et al [21], Ahmad et al [22] 18 Negative perspective towards screening methods (fear, pain, embarrassment, health damage, lack of confidence in test efficacy, inconvenient)…”
Section: Discussionmentioning
confidence: 99%
“…Sung et al [6], Farooqui et al [7], Loh et al [10], Yusoff et al [11], Harmy et al [12], Foo et al [14], Javadzade et al [16], Wong et al [23], Khayyat et al [17], Tastan et al [18], Wong et al [24], Abdullah et al [21], Ahmad [22] 13 'Ostrich strategy'-aversion to facing test results Sung et al [16], Loh et al [10], Yusoff et al [11], Harmy et al [12], Foo et al [14], Javadzade et al [16], Wong et al [23], Bae et al [25], Tastan et al [18], Wong et al [24], Ahmad [22] 11 Financial constraints, lack of insurance coverage Sung et al [6], Farooqui et al [7], Yusoff et al [11], Koo et al [5], Harmy et al [12], Foo et al [14], Deng et al [15], Wong et al [23], Tastan et al [18], Wong et al [24], Abdullah et al [21], Ahmad [23] study subjects, who comprised of Chinese people, were partly attributable to the cultural aversion towards topics regarding the bowel, displaying fecal aversion behavior. This is particularly eminent among the elderly folk.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that majority of the population is not willing to undergo CRC screening in Malaysia 29,30 . The major barriers identified towards uptake of CRC screening were financial constraint, a lack of belief in personal susceptibility, perception that screening is unnecessary as a result of lack of knowledge and, fear of pain and embarrassment 29,31,30,32 . Age, gender, income, and education level were found to be significant determinants of public awareness and knowledge of CRC screening 33 .…”
Section: Overview Of Colorectal Cancer In Malaysiamentioning
confidence: 99%